The Influence of Self Efficacy and Effort on Auditor Performance Specific Experience as Antecedent Variables (Empirical Study on BPK-RI in Indonesia) - Paul Usmany (Budapest International Research and Critics Institute (BIRCI-Journal): Humanities and Social Sciences, 2021)
This study aimed to investigate the effect of specific experience, self efficacy, and effort on auditor’s performance. The study used a model developed from goal setting theory.The study used a survey method on public auditors working at Audit Board of Republic of Indonesia (BPK-RI) headquarters and branch offices in nine different provinces: Jakarta, West Java, Banten, Central Java, Yogyakarta, East Java, Bali, South Sulawesi, and Maluku. The sample of this research is 188 respondents. The data obtained were then analysed by a Structural Equation Model. The study resulted in a positive and significant effect of specific experience on  self efficacy and auditor’s performance; a positive and significant effect of self efficacy on  effort and auditor’s performance; a positive and significant efffect of effort on auditor’s performance.